CLOTH OF FAME (THAUB AS-SYUHRAH) IN ISLAM: JURISPRUDENTIAL AND LINGUISTICAL DISCUSSION WITH RELATION TO CONTEMPORARY HIJAB FASHION - Nurjannah Hasmad; Abdulrahman Alosman (Journal of Islamic, Social, Economics and Development, 2023)
Covering parts of body that is prohibited to be exposed to public or the aurah is one of the obligations in Islam. For majority of Islamic jurisprudential scholars, a Muslim woman’s aurah is her whole body except for her face and palm. In covering her aurah, a Muslim woman must observe that she adheres to all the aurah covering parameters, which include that the cloth that she wears is not among the clothes of fame. This article aims to analyse both the jurisprudential and linguistical aspects of cloth of fame based on the prophetic tradition that mentioned the prohibition of wearing such clothing and relating the topic to some of the phenomenon in contemporary hijab fashion. The text of the hadith is analysed from linguistical point of view based on the words used in it and jurisprudential point of views where the characteristics of fame cloth are extracted from scholar’s discussion regarding the topic. These characteristics are then compared to the features of some phenomenon mingling the fashion industry that also effect the hijab fashion, namely status consumption and fashion uniqueness. This article found out that besides the intangible characteristics of cloth of fame such as the intention of wearing to gain fame, to show-off and to be magnified, the tangible characteristics such as distinguished appearance, high-end extravagance or low-end frugality, finger-pointing nature and being beyond the general norm in the society is as important. This article also argues that status consumption and fashion uniqueness that are occurring in the fashion industry including in the hijab fashion do share the characteristics of fame cloth. Hence, Muslim women should observe not to get involved in these kinds of consumption.